2016
DOI: 10.1002/adma.201506089
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Glass: A Facile Soft Replication Method for Structuring Glass

Abstract: Liquid glass is a photocurable amorphous silica nanocomposite that can be structured using soft replication molds and turned into glass via thermal debinding and sintering. Simple polymer bonding techniques allow the fabrication of complex microsystems in glass like microfluidic chips. Liquid glass is a step toward prototyping of glass microstructures at low cost without requiring cleanroom facilities or hazardous chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 16 publications
0
78
0
Order By: Relevance
“…[29,30] The first successful approach to 3D-printed transparent glass was described by the group of Neri Oxman who used a modified fused deposition modeling approach whereby a low melting soda lime glass was heated to a temperature of ≈1040 °C and the melt was deposited through a nozzle. [34,35] We have shown that these nanocomposites can be printed using benchtop stereolithography in a layer-by-layer based fashion and turned into fused silica glass during a final heat treatment (see Figure 1a). [32] However, both processes result in glass parts with very coarse structures which cannot be used to 3D print chemical reactors or high-resolution microfluidic chips for flow-through synthesis (see Table 1).…”
Section: Transparent Glassmentioning
confidence: 99%
“…[29,30] The first successful approach to 3D-printed transparent glass was described by the group of Neri Oxman who used a modified fused deposition modeling approach whereby a low melting soda lime glass was heated to a temperature of ≈1040 °C and the melt was deposited through a nozzle. [34,35] We have shown that these nanocomposites can be printed using benchtop stereolithography in a layer-by-layer based fashion and turned into fused silica glass during a final heat treatment (see Figure 1a). [32] However, both processes result in glass parts with very coarse structures which cannot be used to 3D print chemical reactors or high-resolution microfluidic chips for flow-through synthesis (see Table 1).…”
Section: Transparent Glassmentioning
confidence: 99%
“…Laser-assisted etching + + 1-2 µm 0.1-0.2 µm (rms) [19][20][21] Backside etching ----2 µm 0.05-0.5 µm [22] Replication Sol-Gel ---< 1 µm n.a. [3] Nanocomposites ---< 1 µm 2 nm (rms) [23,24] Precision glass molding ----~ 1 µm 2 nm [2,25] Additive Stereolithography nanocomposites ++ -60 µm 2 nm (rms) [26] Sol-Gel ++ --200 µm n.a. [27] Stop flow lithography ----10 µm 6 nm (rms) [28] As of today there is no method for generating truly arbitrary three-dimensional hollow structures of centimeter lengths and few micrometers diameter in bulk fused silica glass.…”
Section: Laser-assistedmentioning
confidence: 99%
“…We have recently developed a method for structuring fused silica components at room temperature [23,24,26]. In this process, a nanocomposite consisting of a high amount of fused silica nanoparticles in an organic binder matrix is polymerized at room temperature and consecutively sintered to full-density, transparent fused silica glass.…”
Section: Sacrificial Template Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expensive nature and strict conditions of silicon and glass have restricted the broader application of microfluidics. Recently, a liquid glass has been developed for the fabrication of microfluidic devices without requirement for cleanroom facilities . The low‐cost liquid glass is fabricated by dispersing amorphous silica nanopowder into the photocurable monomer mixture and allows rapid replication under room temperature.…”
Section: Materials For Microfluidic Devicesmentioning
confidence: 99%